Associated factors related to vaccine hesitancy and the intention to vaccinate their children among mothers - Andal, Renee; Jasper Tan, Hugh; Tolentino, Daniel; Legaspi, Louie Fernand D. (Journal of Public Health and Development, 2021)
In 2019, Region IV-A CALABARZON reported the second-highest number of measles cases in the Philippines with 1,086 cases and 25 deaths. Vaccine hesitancy was identified as one of the primary causes of the increase in measles cases. This study aimed to describe the current level of vaccine hesitancy of mothers living in the province of Cavite, to determine factors associated with this hesitancy and their relationships to a mother’s intention to vaccinate their children. Data was collected from 418 respondents using a validated and reliable self-administered survey and processed using IBM SPSS V.24. Spearman’s Rho and Pearson’s R were used to measure correlations. The mothers’ vaccine knowledge (p <0.001) had moderately weak to moderately strong significant relationships to both vaccine hesitancy and intention to vaccinate. Hesitancy and intention had a moderately weak to a moderately strong significant relationship with each other (p <0.001). Educational attainment (p=0.03) and economic (p <0.001) status were less likely to influence vaccine hesitancy and intention to vaccinate as compared to the mothers’ knowledge on vaccinations. The study revealed that as vaccine hesitancy decreases, a mother’s intention to vaccinate their children increases and that as knowledge on the MMR vaccine increases, mothers were less likely to be hesitant towards the vaccination of their children.